Anthropometric Analysis of the Growth Proportions of the Head and Face in Koreans. Issue 1 (20th July 2021) - Yeo, In-Seung; Park, Jung-Ah; Lee, Hye-In; Koh, Ki-Seok; Song, Wu-Chul
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The present study is to identify primarily the morphological characteristics in the growth proportion of the head and face for young Korean (8–24 years) and compare the magnitude of growth changes to the sex-related differences. Total 1255 were divided into 3 age groups: childhood (8–10 years), adolescence (14–16 years), and young adult (20–24 years). The anthropometric assessments were performed with 11 landmarks on the head and facial dimensions. The standardized frontal and lateral head and face photographs were analyzed the craniofacial growth proportions and morphological features for the comparison of both sexes. The noteworthy differences of anthropometric measurements between sexes with growing were noted on the lower head height (22.6%, 17.8%), midface height (22.0%, 19.6%), lower face height (23.5%, 14.7%), and face length (21.1%, 14.9%), face breadth (14.8%, 11.3%) of males and females, respectively. Whereas the upper head height (7.9%, 6.0%) and upper face height (4.2%, 0%, respectively) were less growing features. The most remarkable changes are the dimension of midface height and lower face height in both sexes. The present study could demonstrate a fundamental example to elucidate the sex-related dimensional differences for the analysis of the growth proportion of both sexes in Koreans.